Fitrah Based Education: A Qur'anic Perspective in Developing Children's Natural Potential at Al-Fikri Islamic Fitrah School - noor isna alfaein, noor_isna; Sadiyah, Maemunah; Indra, Hasbi; Handrianto, Budi (LPPM Universitas Ibn Khaldun, Bogor, 2026)
The modern education system has tended to focus on academic achievement. The result is a generation that is intellectually intelligent but lacks empathy and spiritual awareness. The purpose of this study is to identify the concept of fitrah education at the Al-Fikri Islamic School, the implementation of the fitrah education concept at the school, and the ideal holistic concept of fitrah-based education. This research uses a qualitative descriptive method with a case study approach, focusing on examining the background, interactions, and conditions of the Al-Fikri Islamic School. Data collection techniques included interviews with the principal and one Islamic Education teacher. The results of this study are as follows: First, Al-Fikri School demonstrates that the ideal educational process should be oriented toward developing children's natural potential, not merely pursuing academic achievement. Second, the learning process is conducted through a dialogical approach, hands-on practice, activities such as reciting the Qur'an, and the integration of general knowledge with religious knowledge. Third, holistic education aims to shape individuals who reflect the character of the Prophet Muhammad, who are creative, independent, adaptive, and capable of facing the challenges of the times. Keywords: fitrah education, potential, natural